Phosphorylation-dependent BRD4 dimerization and implications for therapeutic inhibition of BET family proteins - Francesca Malvezzi (Nature Portfolio, 2021)
Malvezzi et al. discuss the impact of BRD4 phosphorylation on the formation of dimers and identify the key residues necessary for this dimerization. They also discuss the differential role of monovalent and bivalents bromodomain inhibitors regarding the interaction with these dimers and suggest a new model of BRD4 binding to chromatin.